PENGARUH ORIENTASI PEMBENTUKAN TERHADAP STRUKTUR MIKRO DAN PERILAKU KOROSI PADUAN ALSI10MG YANG DIFABRIKASI DENGAN PELEBURAN LASER SELEKTIF DALAM LARUTAN KOH PADA BERBAGAI KONSENTRASI - Mase Prasasti, Naufal
AlSi10Mg is one of the Al alloys frequently fabricated by additive manufacturing using the selective laser melting (SLM) method. The mechanical properties of SLM-fabricated AlSi10Mg are superior to those of conventionally cast alloys (A360). SLM provides alloys with a very fine microstructure and good silicon phase distribution due to rapid cooling. However, the SLM method also leads to high thermal residual stresses that can affect its corrosion behavior. This research aims to study the effect of different forming orientations during fabrication using the SLM method on the microstructure and corrosion behavior of AlSi10Mg. The corrosion behavior of the specimens was investigated by immersion and electrochemical testing in KOH solutions at different concentrations. The microstructure of the specimens was observed by optical microscopy. Electrochemical testing was carried out by measuring open circuit potential (OCP), cyclic polarization and electrochemical impedance spectroscopy (EIS). The results showed that the building-plane (XY) microstructure has an elongated ?-Al grain microstructure and visible traces of laser direction, while building-direction (XZ) show stacked melt-pool boundaries. Based on electrochemical and immersion testing, the XY plane has better corrosion resistance by 51.52% than the XZ plane due to higher density of the melt-pool boundary in the XZ plane. The OCP values on both planes do not show any significant differences. The results of EIS parameters show pitting occurs only at KOH with 0,005 M concentration for both planes. Cyclic polarization show pitting potential at KOH with 0,005 M and 0,5 M concentrations for both planes and at 2,5 M concentration for XZ plane only. The increase in KOH concentration also affects the corrosion behavior of the alloy where the higher the KOH concentration, the value of the corrosion rate per year will also increase.